Development of Emergency Planning Zones for Ghana’s Proposed Nuclear Plant Based on Radioactivity Releases From Hypothetical Accident Scenarios - Alberta Blay; Sylvester Attakorah-Birikorang; Esi Awuah (Science and Technology of Nuclear Installations)
Emergency planning zones (EPZs) for Ghana’s potential reactor site have been determined based on an assessment of atmospheric dispersion and dose calculations for multiple accident scenarios involving a VVER-1200 reactor. The analysis was performed using the Radiological Assessment System for Consequence Analysis (RASCAL) 4.3.4 code to calculate doses at a downwind distance of 80 km from the site for wet and dry depositions. The highest estimated doses, consistent with the Fukushima accident releases, were used to define the EPZs. The study identified the distances for two main EPZs: precautionary action zones (PAZs) and urgent protective zones (UPZs). The estimated PAZ is 5 km distance around the power plant, requiring evacuation of individuals before radionuclide release begins in the event of a severe accident to prevent deterministic health effects. The UPZ extends approximately 24 km downwind, necessitating the evacuation of affected individuals depending on the release conditions, with priority given to pregnant women, children, and nursing mothers to reduce stochastic health effects. Remaining individuals may need to shelter in their residences or designated centers for two days and take iodine thyroid blocking (ITB) agents within 5–64 km. These EPZs align with the International Atomic Energy Agency (IAEA) recommendations, providing a foundation for policymakers to evaluate the feasibility of proposed emergency measures in developing a robust emergency preparedness and response plan.